A study on the application of total quality management (TQM) priciples among managers in a goverment department in Kuching - Wee, Basil Geok Sang (2003)
The objective of this study is to suggest ways to rectify the problem face by the managers in the overall application of TQM principles in DBKU. It is also to find out the extent of application of this management tool of the managers in the organization on TQM principles. Finally this study aim to find out how successful has DBKU been in assimilating the three TQM principles to the Managers.